Association of plasma levels of Protein S with disease severity in multiple sclerosis. (22nd July 2015) - Ma, Gerry ZM; Giuffrida, Lauren L; Gresle, Melissa M; Haartsen, Jodi; Laverick, Louise; Butzkueven, Helmut; Field, Judith; Binder, Michele D; Kilpatrick, Trevor J
Background: The TAM family of receptor tyrosine kinases (TYRO3, AXL and MERTK) play important roles in modulating innate immune responses and central demyelination. The TAM receptor ligand Protein S (PROS) has also been shown to modulate innate immune cell responses. Objectives: We assessed whether plasma levels of PROS are changed in multiple sclerosis (MS) patients and whether changes are associated with disease severity. Methods: Plasma levels of total and free PROS were measured using enzyme-linked immunosorbent assay in a discovery cohort (MS: 65, control: 14) and an independent replication cohort (MS: 29, control: 29). The Multiple Sclerosis Severity Score (MSSS) was used to evaluate associations between plasma PROS levels and disease severity. Results: We found plasma levels of total, but not free PROS, were decreased in MS patients compared with controls. In female MS patients, we observed decreases in total and free PROS levels compared with controls. In addition, we also observed higher MSSS in patients with very low levels of plasma free PROS. Conclusions: These data suggest PROS may represent a potential marker of disease severity in MS.